On the characterisation of vehicular mobility in a large–scale public transport network. (14th November 2012) - Ahmed, Shabbir; Kanhere, Salil S.
In this paper, we present a thorough characterisation of the spatio–temporal communication graph of a large–scale real–world public transport network. Unlike previous studies, which either use synthetic mobility traces or data from small networks (< 50 nodes), our analysis is based on the mobility patterns of a large–scale (∼1200 nodes) real–world public transport network. In particular, we examine the node degree distribution, encounter patterns, periodicity and clustering behaviour - properties that are particularly relevant in the context of data forwarding in DTN. Our extensive study demonstrates that public transport networks exhibit repetitive patterns and corroborates the existence of few highly connected nodes (termed as hubs). We have also found that the degree distribution of nodes and the inter–contact durations follow the properties of power–law distributions and exhibit moderate to strong self–similarities. We provide insights on how these properties can be leveraged to design effective communication protocols for such large–scale DTN.